Efektivitas public relations dalam meningkatkan loyalitas nasabah bank syariah - Airlangga, Fadil (Maliki Interdisciplinary Journal, 2024)
This study examines the effectiveness of public relations in increasing customer loyalty in Islamic banks. In an era of intense competition, Islamic banks need to build strong relationships with customers to retain and attract new customers. Through a qualitative approach, this study analyzes the public relations strategies implemented by several Islamic banks in Indonesia. Data were collected through interviews with stakeholders, customer surveys, and literature related to PR practices. The results show that good communication, clarity of information and community participation contribute to increasing customer loyalty. Public relations activities such as CSR (Corporate Social Responsibility) programs, seminars and social media are proven to strengthen the emotional bond between banks and customers. In addition, positive perceptions about the nature of Islamic banks created through PR influence consumers’ decisions to use financial services. The results of this study emphasize the importance of a planned and coordinated PR strategy in an effort to increase customer loyalty. Recommendations for better public relations practices in the Islamic financial sector include the importance of monitoring and evaluating public relations practices.